The Lady's Magazine: understanding the emergence of a genre. (September 2017) - King, Nicola
Abstract : A review of the index to the Lady's Magazine, a late 18th- to early 19th-century journal. The index was funded by the Leverhulme Trust. The article examines the structure of the index and discusses approaches to retrieving information.